Characteristics and Outcomes of COVID-19 Patients Admitted to Adult Intensive Care Unit: A Single-Center Observational Study from the Second Wave in Nepal - Pradhan, Saurabh; Upreti, Anup R; Upadhyaya, Sarobar; Oli, Manish; Shrestha, Asim; v, Yashaswi (Journal of Institute of Medicine Nepal, 2021)
Introduction There is inadequate data of critically ill COVID-19 caused by the delta variant. So, we sought to investigate the characteristics and outcomes during the second wave in Nepal. Methods COVID-19 patients admitted to adult ICU of a single institution from April to August 2021 were included. Clinical, laboratory and radiological findings were collected. In-hospital mortality, length of ICU stay, duration of mechanical ventilation (MV) and complications during ICU stay were obtained. Results Total 136 patients were included with a mean age of 56.24 (± 15.81) years and 52.2% males. Fifty-five percent had comorbidities. Mean fraction of inspired oxygen required was 0.8 and sequential organ failure assessment score on admission was 4.09. C-reactive protein (CRP), lactate dehydrogenase and ferritin levels were elevated to 62.5mg/L, 515 U/L and 472ng/mL respectively. The computed tomography score was 20. Thirty four (25%) required MV; 70 (52%) were managed with non-invasive ventilation; 41 (30.14%) required vasopressors; 4 (2.9%) required renal replacement therapy. In-hospital mortality was 43.4%. The median length of ICU stay and duration of MV were 6 and 3.5 days respectively. Hospital acquired infection was the commonest complication. Age (OR 1.126 (95% CI 1037-1.223, p value 0.005)) and CRP on admission (OR 1.023 (95% CI 1.000-1.047, p value 0.050) were found to be predictors of mortality. Conclusion In this single center study from the second wave of the pandemic, majority of critically ill COVID-19 patients were elderly with co-existing illnesses. In-hospital mortality was high. Age and CRP on admission were found to be independently associated with poor outcome.